Kepemimpinan Efektif dalam Lembaga Pendidikan - Sitepanus Zebua (Journal New Light, 2025)
In this study, the researcher examines in depth the concept and application of various research approaches in various previous scientific studies. The study materials are theoretical studies and previous research results from books, national journals and international journals. The author uses data analysis with a descriptive qualitative approach. The results of the study indicate that effective leadership in educational institutions has been able to find new truths and knowledge for the development of leadership that is beneficial to human life.